1981
DOI: 10.1111/j.1476-5381.1981.tb10433.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on 5‐hydroxytryptamine Transport in Pancreatic Islets and Isolated Β‐cells

Abstract: The transport mechanism for 3H‐labelled 5‐hydroxytryptamine (5‐HT) in isolated pancreatic islets of non‐inbred ob/obmice was further characterized. Isolated β‐cells accumulated 5‐HT to the same degree and with the same Na+‐dependence as whole islets. Imipramine inhibited the uptake in a concentration‐dependent way. Reserpine did not affect the uptake or efflux rates. Glucose stimulation of insulin secretion did not affect the uptake rate. It is concluded that the observed islet uptake of [3H]‐5‐HT represents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Similarly, (+)-dihydrotetrabenazine, a substrate for the vesicular monoamine transporter 2 (VMAT2), has been explored for isletspecific imaging in vivo and drug delivery (Hao et al, 2016) However, VMAT2 expression may be insufficiently selective for b-cell-directed drug delivery (Eriksson et al, 2016). Likewise, the compound [ 11 C]5-hydroxytryptophan (HTP), which is selectively accumulated in the endocrine pancreas via the large amino acid transporter, was used to assess b-cell mass (Lindstro ¨m, 1981). However, rapid degradation of HTP-based probes by monoamine oxidase A may limit the feasibility of HTP-dependent islet targeting (Eriksson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, (+)-dihydrotetrabenazine, a substrate for the vesicular monoamine transporter 2 (VMAT2), has been explored for isletspecific imaging in vivo and drug delivery (Hao et al, 2016) However, VMAT2 expression may be insufficiently selective for b-cell-directed drug delivery (Eriksson et al, 2016). Likewise, the compound [ 11 C]5-hydroxytryptophan (HTP), which is selectively accumulated in the endocrine pancreas via the large amino acid transporter, was used to assess b-cell mass (Lindstro ¨m, 1981). However, rapid degradation of HTP-based probes by monoamine oxidase A may limit the feasibility of HTP-dependent islet targeting (Eriksson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Externally added 5-HT is incorporated into the B cells of ob/ob mice [15][16][17][18]. The precursor, 5-HTP, is taken up and rapidly converted to 5-HT ]12-14].…”
Section: Discussionmentioning
confidence: 99%
“…Islet cells can accumulate and store 5-HT intracellularly [12][13][14] and the effects of elevation of intracellular 5-HT have been studied. Such elevation can be achieved in two ways; the B cells can take up and effectively decarboxylate the precursor, 5-hydroxytryptophan (5-HTP) [12][13][14] or they can accumulate exogenously added 5-HT [15][16][17][18]. The 5-HT accumulated is only slowly metabolized by the islets [14].…”
mentioning
confidence: 99%
“…The transport process operative under these conditions appeared to be principally one of diffusion. Studies with mouse islet cells (Lindstrom, 1981) have indicated that at submicromolar 5-hydroxytryptamine concentrations there is a second Na+-dependent 5-hydroxytryptamine uptake process that may correspond to the high-affinity uptake system that is present in brain tissue (Ross & Renyi, 1967). There was no evidence of this, however, in our experiments.…”
Section: Cellular Uptake Studiesmentioning
confidence: 99%
“…Investigation of the net uptake of 5-hydroxytryptamine radioactivity by intact islets and by dispersed islet cells from ob/ob mice has suggested the functioning in the B-cell of a high-affinity Na+-dependent 5-hydroxytryptamine transport system of low capacity together with a low-affinity non-saturable transport process (Lindstrom et al, 1980;Lindstrom, 1981). Considerable variation is evident in the uptake rates in different species (Mahoney & Feldman, 1977).…”
mentioning
confidence: 99%